Chronic Osteomyelitis After a Partial Internal Fixation Surgery: A Case Report - Elvina Prisila; Moch. Junaedy Heriyanto (Universitas Ahmad Dahlan, 2022)
Chronic osteomyelitis is a condition of acute osteomyelitis that has failed to heal because appears as long-lasting and refractory disease in which bacteria may produce biofilms consisting of matrix proteins and polysaccharides to protect the bacteria from antibiotics and monocyte-macrophage system obliteration.1,2 We report a 40-years-old man with a history of postoperative open fracture of the right femur 6 months ago. Pain (+). X-ray examination showed the results: attached plate and screw with nonunion old fracture of the femoral dextra alignment and less apposition with sclerotic features, osteodestruction of the left femoral system, leading to osteomyelitis. Then performed a partial internal fixation removal operation. From the results obtained from the patient, it was concluded that there was osteomyelitis in the femur due to complications from a postoperative open fracture of the right femur.